Quantization error in magnetic resonance imaging. (May 2014) - Cadiz, Rodrigo F.; Muñoz, Camila; Tejos, Cristian; Andia, Marcelo E.; Uribe, Sergio; Irarrazaval, Pablo
ABSTRACT: Due to the special nature of the acquisition domain, the quantization process of magnetic resonance imaging (MRI) data presents challenges that are not present in other medical imaging techniques. In this article, we demonstrate that the quantization error in MRI cannot be assumed to be a random variable with uniform distribution across the entire acquisition domain. Furthermore, the introduced error is not statistically independent of the input signal. On the contrary, we show that this error is correlated with the object that is being scanned, producing perceptually unpleasant artifacts in the image domain. Although the quantization error is not generally a critical issue in two‐dimensional (2D) MRI acquisition, it could be in the case of 3D acquisitions and in noise estimation measurements. © 2014 Wiley Periodicals, Inc. Concepts Magn Reson Part A 43A: 79–89, 2014.